Effect of Intracameral Cefuroxime Injection in Prophylaxis of Postoperative Endophthalmitis - Hassan Razmju; Hossein Attarzadeh; Hosseiali Esmaeili (مجله دانشکده پزشکی اصفهان, 2011)
• endophthalmitis provide very different results concerning the incidence and prophylaxis of this very severe complication of cataract surgery. This study aimed to present the outcomes of prophylaxis of postoperative endophthalmitis following cataract surgery with intracameral cefuroxime. • Methods: In this study, 11500 patients underwent cataract surgery were selected from our patients attending Sadra clinic and Feiz hospital in Isfahan. All patients underwent phacoemulsification cataract surgery. Case group received an injection of 0.1 ml intracameral cefuroxime at the end of surgery. The data collected in check list and were analyzed by chi-square with SPSS software. • Finding: The mean age in patients was 55.2 ± 6.7 years with the range 22-87 years. 5958 patients recieved intracameral cefuroxime and 5542 patients did not. The rate of postoperative endophthalmitis in case group was less than the control group (P < 0.05). • Conclusion: Intraocular cefuroxime acts very well for reducing the incidence of postoperative endophthalmitis. It appears safe to use and is easy to prepare.